2010
DOI: 10.1177/1046496409356480
|View full text |Cite
|
Sign up to set email alerts
|

Are Group Leader Knowledge Structures Related to Member Satisfaction With the Leader?

Abstract: Knowledge structures are people’s ways of organizing the concepts in a domain. Educational effectiveness can be documented by examining changes in novices’ knowledge structures. Studies show that group counseling trainees begin to structure their knowledge of group members and group leader interventions in a manner similar to the knowledge structure of experienced group counselors. This research assumes that trainees with knowledge structures more similar to experienced practitioners will be more effective gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…In addition, when therapists-in-training were more like experts in terms of seeing comprehensive and meaningful patterns in counseling data, their clients reported deeper and smoother sessions and greater therapist attractiveness, trustworthiness, and expertness (Kivlighan, 2008). Similarly, when group therapists-in-training increasingly became like experts in terms of seeing comprehensive and meaningful patterns in group counseling data, group members reported greater satisfaction with leadership (Kivlighan & Kivlighan, 2010). Furthermore, group therapy trainees who observed expert therapists, were observed by experts, and received feedback developed more complex, deeper, and more integrated knowledge structures about group members (Kivlighan, Markin, Stahl, & Salahuddin, 2007) and group leader interventions (Kivlighan & Kivlighan, 2009).…”
Section: Criteria For Assessing Expertisementioning
confidence: 99%
“…In addition, when therapists-in-training were more like experts in terms of seeing comprehensive and meaningful patterns in counseling data, their clients reported deeper and smoother sessions and greater therapist attractiveness, trustworthiness, and expertness (Kivlighan, 2008). Similarly, when group therapists-in-training increasingly became like experts in terms of seeing comprehensive and meaningful patterns in group counseling data, group members reported greater satisfaction with leadership (Kivlighan & Kivlighan, 2010). Furthermore, group therapy trainees who observed expert therapists, were observed by experts, and received feedback developed more complex, deeper, and more integrated knowledge structures about group members (Kivlighan, Markin, Stahl, & Salahuddin, 2007) and group leader interventions (Kivlighan & Kivlighan, 2009).…”
Section: Criteria For Assessing Expertisementioning
confidence: 99%
“…The Closeness among the four expert group counselor, computed by the Pathfinder measure of concept relatedness ranged from .39 to .42 (all p s < .001). These structural similarity coefficients were larger than the .26 coefficient reported in Davis and Yi (2004) or the average Closeness of .31 reported for six computer science experts in Acton, Johnson, and Goldsmith (1994); but somewhat smaller than the average Closeness of .52 between three experienced group therapists in the Kivlighan and Kivlighan (2010). The correlations and Closeness coefficients suggest that the four experts shared a common conception of effective group leadership.…”
Section: Methodsmentioning
confidence: 60%
“…After training, the novices' knowledge structures became more complex and hierarchical, as evidenced by more circular patterns among the leadership interventions. Kivlighan and Kivlighan (2010) also used the revised Group Therapy Questionnaire (GTQ; Wile et al, 1970; Wile, 1973) to examine group leader trainees' knowledge structures of group leader interventions. They found that group member satisfaction with the leader was positively related to similarity between novice group counselors' knowledge structures and those of expert group counselors.…”
Section: Knowledge Structures Of Group Counseling Experts and Novice ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A related limitation is that our study examined only CI reports of trainees, and thus the clusters of CIs we found may not hold in more expert facilitator samples. Indeed, the literatures on the experiences of expert group counselors (e.g., Rubel & Kline, 2008) and on the development of expertise in group counseling trainees (Kivlighan & Kivlighan, 2010) suggest that there are meaningful experiential and cognitive shifts that occur through training and gaining experience. Future cross-sectional research should examine CI reports of trainee IGD facilitators compared with more expert facilitators.…”
Section: Discussionmentioning
confidence: 99%